The intriguing case of Was 49b. Issue Volume 15:Issue S359(2020) (March 2019) - Schmitt, Henrique R.; Secrest, Nathan J.; Blecha, Laura; Rothberg, Barry; Fischer, Jacqueline
Abstract: We present results of a multiwavelength study of the isolated dual AGN system Was 49. Observations show that the dominant component in this interacting system, Was 49a, is a spiral galaxy, while Was 49b is hosted in a dwarf galaxy located at 8 kpc from the nucleus of Was 49a, at the edge of its disk. The intriguing fact about this system is the luminosity of their corresponding AGNs. While Was 49a hosts a low luminosity Seyfert 2 with L bol ˜10 43 erg s –1, Was 49b has a Seyfert 2 with L bol ˜ 10 45 erg s –1, in the luminosity range of Quasars. Furthermore, estimates of the black hole and host galaxy masses of Was 49b indicate a black hole significantly more massive than one would expect from scaling relations. This result is in contrast with findings that the most luminous merger-triggered AGNs are found in major mergers and that minor mergers predominantly enhance AGN activity in the primary galaxy.